Depressive symptoms are no longer a barrier to HCV treatment initiation in the HIV–HCV co-infected population in Canada. Issue 1 (5th February 2022) - Marathe, Gayatri; Moodie, Erica E M; Brouillette, Marie-Josée; Cox, Joseph; Delaunay, Charlotte Lanièce; Cooper, Curtis; Hull, Mark; Gill, John; Walmsley, Sharon; Pick, Neora; Klein, Marina B; ,
Background: Psychiatric illness was a major barrier for HCV treatment during the Interferon (IFN) treatment era due to neuropsychiatric side effects. While direct acting antivirals (DAA) are better tolerated, patient-level barriers persist. We aimed to assess the effect of depressive symptoms on time to HCV treatment initiation among HIV–HCV co-infected persons during the IFN (2003–2011) and second-generation DAA (2013–2020) eras. Methods: We used data from the Canadian Co-infection Cohort, a multicentre prospective cohort, and its associated sub-study on Food Security (FS). We predicted Center for Epidemiologic Studies Depression Scale-10 (CES-D-10) classes for depressive symptoms indicative of a depression risk using a random forest classifier and corrected for misclassification using predictive value-based record-level correction. We used marginal structural Cox proportional hazards models with inverse weighting for competing risks (death) to assess the effect of depressive symptoms on treatment initiation among HCV RNA-positive participants. Results: We included 590 and 1127 participants in the IFN and DAA eras. The treatment initiation rate increased from 9 (95% confidence interval (CI): 7–10) to 21 (95% CI: 19–22) per 100 person-years from the IFN to DAA era. Treatment initiation was lower among those with depressive symptoms compared to those without in the IFN era (hazard ratio: 0.81 (95% CI: 0.69–0.95)) and was higher in the DAA era (1.19 (95% CI: 1.10–1.27)). Conclusion: Depressive symptoms no longer appear to be a barrier to HCV treatment initiation in the co-infected population in the DAA era. The higher rate of treatment initiation in individuals with depressive symptoms suggests those previously unable to tolerate IFN are now accessing treatment.